Application of computer vision in the assessment of the in vitro development of Oncidium sphacelatum Lindl., (Orchidaceae) protocorms - Vincenzo Bertolini; Javier Francisco Valle Mora; Ángel Natanael Rojas Velázquez (Acta Agronómica)
We report an application of computer vision designed to monitor the in vitro development of Oncidium sphacelatum Lindl., orchid protocorms. Growth and development of protocorms was evaluated in terms of size (measured through the area in pixels), changing in its shape within the germination process (measured by the roundness factor) and state of health (color tone), using digital photos. Programming the software Matlab R2012a, we developed a type of analysis, consists of a first stage as segmentation to discern the pixels of interest (protocorms), a second stage of training and learning to establish criteria for segregation of interest object and a final stage as classification. Programming is performed by R2012a Matlab platform. The characteristics obtained by our system provide useful information for evaluating the germination process of in vitro propagation by orchid grains, with significant savings in terms of hours/work of the human operator.